Analisis validasi lks berorientasi HOTS dalam model inkuiri terbimbing pada materi gerak lurus, gerak parabola dan gerak melingkar - Resti Novela; Silvi Yulia Sari; Yenni Darvina (Universitas Negeri Padang, 2019)
Physics is a subject that can produce young people who are productive, creative, innovative. Physics lessons require students to understand and solve existing environmental problems in real life. With the ability to think critically, creatively, collaboratively, and communicate can be developed to equip students to face challenges in the 21st century. However, the real conditions in schools show that physics is not running optimally. To help the learning process, learning resources are needed. One of the learning resources needed to overcome this problem is teaching material in the form of Student Worksheets. The purpose of this study is to determine the validity of HOTS-Oriented Student Worksheets in the guided inquiry model. This type of research is Research and Development (R&D) using the Brog and Gall model. The object of the research was HOTS-oriented Student Worksheets in guided inquiry models on the material of Straight Motion, parabolic motion, and circular motion in class X SMA / MA. The results of the research data were obtained from the results of the validity of 3 physics lecturers from the Faculty of Mathematics and Natural Sciences UNP. Based on data analysis from the research that has been done, it can be concluded that the average value of HOTS-oriented worksheet validation in the guided inquiry model in the material of straight motion, parabolic motion, and circular motion is 82.3. Thus HOTS-oriented behavior in guided inquiry models in the material of straight motion, parabolic motion, and circular motion is at a very high level of validity.